The Doubters' Dilemma Exploring student attrition and retention in university language and culture programs - Martín, Mario Daniel (ANU Press, 2016)
This book explores the extent and causes of attrition and retention in university Language & Culture (L&C) programs through a detailed analysis of an institutional case study at The Australian National University (ANU). Using extensive data collected through student surveys, coupled with data mining of university-wide enrolment data, the authors explore the enrolment and progress of students in all ANU L&C programs. Through their detailed statistical analysis of attrition and retention outcomes, the authors reveal serious inadequacies in the traditional, and common, methodology for determining the extent of student attrition and retention in tertiary L&C programs. Readers are shown why a year-to-year comparison of students who continue or discontinue language studies using traditional statistical methodology cannot provide data that is sufficiently meaningful to allow for sound policy- and decision-making. The authors instead suggest a more valid, replicable methodology that provides a new approach potentially applicable to all disciplines and all student retention measures. The authors also demonstrate that the empirical data supports a new hypothesis for the reasons for attrition, based on students' relative belief or doubt in their capacity to complete their studies successfully. By highlighting the importance of language capital as a factor in students' concerns about their capacity for success, and hence in their decisions to stay in, or leave, a university language program, the authors show the importance of the 'doubters' dilemma'. By taking a rigorous approach to hypothesis building and testing around enrolment and attrition data, the authors provide valuable insights into attrition issues, and potential retention strategies, in L&C programs, which will be relevant to institutions, policy-makers and teaching academics.